Shaving composition

JP7638641B2Active Publication Date: 2025-03-04DAIO PAPER CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020135902
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-11
Publication Date
2025-03-04
Estimated Expiration
2040-08-11

AI Technical Summary

Benefits of technology

【0017】 本発明によると、発泡安定性に優れるシェービング剤組成物になる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638641000004
    Figure 0007638641000004
  • Figure 0007638641000001
    Figure 0007638641000001
  • Figure 0007638641000002
    Figure 0007638641000002
Patent Text Reader

Abstract

To provide a shaving agent composition having excellent foaming stability.SOLUTION: A shaving agent composition contains fine fibers with an average fiber width of 1-1000 nm, and a foaming component.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a shaving agent composition suitable for use as a foaming shaving agent such as a shaving foam or a shaving gel foam. [Background technology]

[0002] Shaving agents used when shaving body hair such as beards and unwanted hair with a razor or the like include solid or powder shaving soaps using fatty acids such as soap, shaving creams, shaving gels, aerosol-type shaving foams, and post-foaming shaving gel foams.

[0003] Proposals for such shaving agents include, for example, one that aims to achieve high transparency in the gel-like discharged product (see Patent Document 1). However, the essential challenge for shaving agents is still how to reduce stress on the skin. In particular, in the case of foaming (type) shaving agents, it is required that they foam a large amount, i.e., they foam sufficiently, and the foamed foam is stable over time.

[0004] In this regard, there has been a proposal for foaming shaving agents by dissolving compressed gas in the shaving agent (see Patent Document 2). This proposal has also been evaluated as resulting in a greater foaming amount in shaving agents that dissolve less compressed gas and use a post-foaming agent such as pentane (see Patent Document 1). However, as mentioned above, in addition to the foaming problem, there is also the problem of foam stability (foam maintenance). This problem (foam stability problem) cannot be solved by simply deciding whether to use a post-foaming agent or compressed gas. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 7-163861 [Patent Document 2] Japanese Patent Application Publication No. 2-247115 Summary of the Invention [Problem to be solved by the invention]

[0006] The main problem to be solved by the present invention is to provide a shaving composition that has excellent foaming stability. [Means for solving the problem]

[0007] The means for solving the above problems are as follows. (Means described in claim 1) The fiber contains cellulose fine fibers having an average fiber width of 1 to 1,000 nm and an axial ratio of 10 to 340,000, and a foaming component. fruit , The cellulose fine fibers include fine fibers in which some or all of the hydroxy groups have been modified with an ester of phosphorus oxoacid, and unmodified fine fibers, containing sulfonic acid type surfactants, A shaving composition comprising:

[0008]

[0009] (Claim 2 (Means described in the phosphorus oxoacid is phosphorous acid, the amount of the phosphorous acid ester incorporated is greater than 2.0 mmol / g; Claim 1 The shaving composition according to claim 1.

[0010] (Claim 3 (Means described in The foaming component contains at least one anionic surfactant selected from a carboxylic acid type surfactant, a sulfonic acid type surfactant, a sulfate ester type surfactant, a phosphate ester type surfactant, and an amino acid type surfactant. Claim 1 or claim 2 The shaving composition according to claim 1.

[0011]

[0012]

[0013] (Claim 4 (Means described in The crystallinity of the cellulose fine fibers is 50 to 100%. Claim 1~ 3 A shaving composition according to any one of the preceding claims.

[0014] (Claim 5 (Means described in The dispersion liquid having a concentration of the cellulose fine fibers of 1% by mass has a Brookfield viscosity of 1,000 to 200,000 cps. Claim 1~ 4 A shaving composition according to any one of the preceding claims.

[0015] (Claim 6 (Means described in The average fiber length of the cellulose fine fibers is 3 to 5000 μm. Claim 1~ 5 A shaving composition according to any one of the preceding claims.

[0016] (Claim 7 (Means described in The phosphorous content of the entire composition acid The proportion of modified fine fibers is 1 to 20% by mass. Claim 2 The shaving composition according to claim 1. [Effects of the Invention]

[0017] According to the present invention, a shaving composition having excellent foaming stability is obtained. [Brief explanation of the drawings]

[0018] [Figure 1] FIG. 10 is a diagram for explaining a method for evaluating foam viscosity. DETAILED DESCRIPTION OF THE INVENTION

[0019] Next, a description will be given of an embodiment of the invention. Note that this embodiment is an example of the present invention. The scope of the present invention is not limited to the scope of this embodiment. Furthermore, unless otherwise specified, the blending ratios shown below refer to the ratios of all ingredients including water and not the active ingredients.

[0020] The shaving agent composition of this embodiment contains fine fibers having an average fiber width of 1 to 1,000 nm and a foaming component. Preferably, the fine fibers are fine fibers in which some or all of the hydroxy groups have been modified with a phosphorus oxoacid ester, more preferably at least one of phosphorous acid-modified fine fibers modified with a phosphorous acid ester and unmodified fine fibers. In particular, when unmodified fine fibers are included, a sulfonic acid surfactant is also included. In addition to the fine fibers, the foaming component usually contains a surfactant, and if necessary, a post-foaming agent, a foaming aid such as compressed gas, and the like. These will be explained in order below.

[0021] In addition, the shaving agent composition of this embodiment may be in foam form (foam-like) when discharged from a pressure-resistant container such as a double pressure-resistant container, a tube, a bottle, or other container, or may be in gel form that subsequently foams (post-foaming).

[0022] (Surfactant as a foaming component) The shaving agent composition of this form is, for example, sprayed as a shaving agent, or initially discharged as a gel, but then lathers to form a foam using foaming ingredients such as foaming (foaming) surfactants and post-foaming agents.

[0023] Examples of foaming surfactants include carboxylic acid type (preferably fatty acid salts such as laurate, stearate, palmitate, etc.), sulfonic acid type (preferably α-olefin sulfonic acid), sulfate type, phosphate type, and amino acid type surfactants.

[0024] In this embodiment, since the shaving agent composition contains fine fibers, the foaming component can be only a foaming surfactant. In other words, when a foaming surfactant is used, the use of a post-foaming agent or foaming gas can be omitted. However, when it is desired to further promote foaming (foaming), it is also preferable to use a post-foaming agent or foaming gas as a foaming assistant (in combination with a foaming surfactant).

[0025] The blending ratio of the foaming surfactant is preferably 1 to 30% by mass, more preferably 2 to 20% by mass. If the blending ratio is less than 1% by mass, foaming properties may decrease. On the other hand, if the blending ratio is more than 30% by mass, excessive foaming may occur, which may cause excessive irritation to the skin.

[0026] Here, foaming surfactants will be described in detail. Foaming surfactants include ionic surfactants, which dissociate and become ionized when dissolved in water, and nonionic surfactants. Ionic surfactants are further divided into anionic surfactants, cationic surfactants, and amphoteric surfactants. In the present invention, anionic surfactants and amphoteric surfactants are preferably used as foaming surfactants.

[0027] Examples of foaming anionic surfactants that can be used include, for example, carboxylates such as laurates, stearates, palmitates, and myristates; sulfonates such as α-olefin sulfonates, sulfosuccinates, and α-sulfofatty acid methyl ester salts; polyoxyethylene alkyl sulfates such as sodium polyoxyethylene lauryl ether sulfate and polyoxyethylene lauryl ether triethanolamine sulfate; N-acylamino acid salts such as sodium lauroyl sarcosine and sodium lauroyl methyl alanine; and polyoxyethylene alkyl ether phosphates such as sodium polyoxyethylene lauryl ether phosphate, polyoxyethylene cetyl ether sodium phosphate, dipolyoxyethylene alkyl ether phosphate, tripolyoxyethylene alkyl ether phosphate, dipolyoxyethylene nonylphenyl ether phosphate, sodium polyoxyethylene lauryl ether phosphate, and sodium dipolyethylene lauryl ether phosphate.

[0028] However, it is preferable to use at least one surfactant selected from carboxylic acid type surfactants, sulfonic acid type surfactants, sulfate ester type surfactants, phosphate ester type surfactants, and amino acid type surfactants as the foaming surfactant.

[0029] Furthermore, when unmodified fine fibers are used as the fine fibers, it is preferable to use a sulfonic acid surfactant, and it is more preferable to use a sulfonate such as an α-olefin sulfonate. When unmodified fine fibers are used, the use of a sulfonic acid surfactant results in high foaming properties and improved foam strength, thereby increasing foam stability (foam retention). Note that the sulfonic acid surfactant refers to a surfactant containing sodium sulfonate, and examples of alpha-olefin surfactants include sodium α-olefin sulfonate and normal paraffin surfactants include sodium alkyl sulfonate.

[0030] As the foaming amphoteric surfactant, for example, one or more selected from alkylbetaine, alkylamidobetaine, alkylsulfobetaine, etc. can be used.

[0031] Examples of nonionic surfactants that can be used include polyoxyethylene hydrogenated castor oil; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monostearate and polyoxyethylene sorbitan tetraoleate; polyoxyethylene glyceryl fatty acid esters such as polyoxyethylene glyceryl monoisostearate and polyoxyethylene glyceryl triisostearate; polyethylene glycol fatty acid esters such as polyethylene glycol monoisostearate; polyoxyethylene adduct surfactants such as polyoxyethylene alkyl ethers such as polyoxyethylene hexyldecyl ether, polyoxyethylene octyldodecyl ether, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, and polyoxyethylene nonylphenyl ether; polyglycerin surfactants such as polyglycerin alkyl ethers and polyglycerin fatty acid esters; and silicone derivative surfactants such as polyoxyethylene methylpolysiloxane copolymers and poly(oxyethylene-oxypropylene)methylpolysiloxane copolymers.

[0032] Nonionic surfactants may also be used to improve the emulsification or dispersibility of the composition. These nonionic surfactants preferably have an HLB of 10 or more, more preferably 11 or more, and particularly preferably 12 or more, which indicates the degree of affinity of the surfactant for water and oil (a water-insoluble organic compound). If the HLB is less than 10, the dispersibility of the composition may be poor.

[0033] Examples of nonionic surfactants with an HLB of 10 or more include POE alkyl ethers such as polyoxyethylene (hereinafter POE) (9) lauryl ether [HLB (hereinafter the same): 14.5], POE (7) cetyl ether [11.5], POE (20) stearyl ether [18.0], POE (7) oleyl ether [10.5], and POE (20) behenyl ether [18.0]; POE·POP alkyl ethers such as POE (10) polyoxypropylene (POP) (4) cetyl ether [10.5] and POE (20) POP (6) decyl tetradecyl ether; polyethylene glycol monolaurate (10E.O.) [12.5]; monosodium benzoate; Polyethylene glycol fatty acid esters such as polyethylene glycol tearate (10E.O.) [11.0] and polyethylene glycol monooleate (10E.O.) [11.0], POE castor oils and hydrogenated castor oils such as POE (20) castor oil [10.5] and POE (30) hydrogenated castor oil [11.0], and POE sorbitan fatty acid esters such as POE (20) sorbitan monococonut oil fatty acid [16.9], POE (20) sorbitan monopalmitate [15.6], POE (20) sorbitan monostearate [14.9] and POE (20) sorbitan monooleate [15.0] can be used alone or in combination of two or more.

[0034] In the shaving composition of this embodiment, by using a fatty acid and an alkaline agent, a foaming surfactant can be contained.

[0035] As the fatty acid, for example, a linear or branched, saturated or unsaturated fatty acid having 10 to 22 carbon atoms (preferably 12 to 18) can be used. Specific examples include fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, behenic acid, isostearic acid, linoleic acid, linolenic acid, and ricinoleic acid, as well as fatty acids derived from natural fats and oils containing these fatty acids. These fatty acids can be used alone or in combination of two or more. However, it is preferable to use linear fatty acids such as myristic acid, palmitic acid, and stearic acid, and coconut oil fatty acids containing these fatty acids.

[0036] The fatty acid is usually contained as a soap, which is preferably produced by blending a higher fatty acid and an alkaline agent.

[0037] As the higher fatty acid, for example, one or a combination of two or more of stearic acid, palmitic acid, myristic acid, lauric acid, etc. can be used.

[0038] The blending ratio of the higher fatty acid is preferably 2 to 30% by mass based on the total mass of the composition.

[0039] To neutralize the fatty acids, it is preferable to add an alkaline agent. Examples of alkaline agents that can be used include organic bases such as alkanolamines and basic amino acids, and inorganic bases such as alkali metal hydroxides. Specifically, examples of alkanolamines that can be used include triethanolamine and 2-amino-2-methyl-1-propanol, basic amino acids such as arginine, lysine, and histidine, and alkali metal hydroxides such as sodium hydroxide and potassium hydroxide. However, in this embodiment, in which fine fibers are used, it is preferable to use sodium hydroxide.

[0040] (Post-foaming agent) As the post-foaming agent, normal pentane or isopentane is preferably used, although other post-foaming agents such as isobutane and normal butane can also be used.

[0041] The blending ratio of the post-foaming agent is preferably 1 to 20% by mass, more preferably 1 to 15% by mass, and particularly preferably 1 to 10% by mass. If the blending ratio is less than 1% by mass, the amount of foaming may be insufficient. On the other hand, if the blending ratio exceeds 20% by mass, the amount of foaming may be too much, and stability of foaming over time may not be obtained even in this embodiment containing fine fibers.

[0042] (compressed gas) In this embodiment, compressed gas can be contained as a foaming component in place of or together with the post-foaming agent.

[0043] As the compressed gas, for example, one or more gases selected from carbon dioxide gas, nitrogen gas such as nitrogen sulfite gas, oxygen gas, argon gas, helium gas, neon gas, and the like can be used.

[0044] (others) The shaving composition of this embodiment is usually blended with water, which may be tap water, distilled water, ion-exchanged water, purified water, or the like.

[0045] The blending ratio of water is, for example, 40 to 95 mass %, and preferably 45 to 90 mass %, based on the total mass of the composition.

[0046] The shaving composition of this embodiment may contain, as appropriate, ingredients other than the fine fibers described below, such as moisturizers, preservatives, pH adjusters, viscosity adjusters, antioxidants, cooling agents, disinfectants, fragrances, colorants, etc. The fine fibers described in detail below also function as viscosity adjusters.

[0047] (fine fibers) The shaving agent composition of this embodiment has improved viscosity due to the fine fibers, resulting in improved foaming properties and uniform foaming throughout the composition, preventing the composition from remaining as a gel on the skin (when used as a slow-foaming, post-foaming composition). Furthermore, the improved viscosity due to the fine fibers also results in excellent foaming stability. When used as a slow-foaming, post-foaming composition, the gel (discharged material) dispensed onto the skin gradually foams and forms a foam when gently rubbed.

[0048] The shaving agent composition of this embodiment contains, as fine fibers, phosphorus oxo acid-modified fine fibers, more preferably at least one of phosphorous acid-modified fine fibers and unmodified fine fibers. However, when unmodified fine fibers are contained, it is preferable to use a sulfonic acid-type surfactant as described above. When a sulfonic acid-type surfactant is used, initial foaming is high, as will be apparent from the examples described below. In the case of phosphorus oxo acid-modified fine fibers containing phosphorous acid, foaming stability is extremely excellent regardless of which surfactant is used.

[0049] In this embodiment, "unmodified" refers to cellulose fibers that have not been chemically modified, such as by TEMPO oxidation, modification with phosphorus oxoacids such as phosphoric acid and phosphorous acid, or carbamate modification. In this regard, chemically modified cellulose raw materials generally result in higher uniformity of cellulose nanofibers obtained by subsequent defibration. However, when a sulfonic acid surfactant is used, the use of unmodified cellulose fibers can suppress the effects of electrostatic repulsion, resulting in excellent initial foamability and foam stability. However, when unmodified fine fibers are used alone, elasticity tends to be poor. On the other hand, when a sulfonic acid surfactant is used, the use of phosphorous acid-modified fine fibers alone tends to result in poor foamability. Therefore, it is preferable to use phosphorous acid-modified fine fibers and unmodified fine fibers separately, taking into account initial foamability, foam stability, elasticity, usable surfactants, etc. From this perspective, when both phosphorous acid-modified fine fibers and unmodified fine fibers are used in combination, the blending ratio, by mass, when a sulfonic acid surfactant is used, is, for example, 1:1 to 10, preferably 1:1 to 5, and more preferably 1:1 to 3. On the other hand, when a surfactant other than a sulfonic acid surfactant is used, the ratio is, for example, 1:1 to 10, preferably 1:1 to 8, more preferably 1:1 to 6, on a mass basis.

[0050] In the present invention, the term "unmodified" is defined as meaning that the hydroxyl groups on the surface of the cellulose fibers are not modified.

[0051] On the other hand, in the phosphorous acid-modified fine fibers, some or all of the hydroxy groups (-OH groups) of the cellulose fibers are modified with a phosphorous acid ester. Preferably, some or all of the hydroxy groups are substituted with a functional group represented by the following structural formula (1), thereby introducing (modifying or modifying) a phosphorous acid ester. Particularly preferably, some of the hydroxy groups of the cellulose fibers are substituted with a carbamate group, thereby also introducing a carbamate (an ester of carbamic acid).

[0052] [ka]

[0053] In structural formula (1), α is either none, R, or NHR. R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, or a derivative thereof. β is a cation composed of an organic or inorganic substance.

[0054] Phosphorous acid esters are compounds in which a hydroxyl group (-OH) and an oxo group (=O) are bonded to a phosphorus atom, and the hydroxyl group provides an acidic proton. Therefore, phosphorous acid esters have a high negative charge, similar to compounds having a phosphate group. Therefore, the introduction of phosphorous acid esters strengthens the repulsion between cellulose molecules, facilitating the defibration of cellulose fibers. Furthermore, the introduction of phosphorous acid esters improves the transparency and viscosity of the dispersion. Furthermore, phosphorous acid-modified fine fibers are also cellulose fine fibers, and cellulose fine fibers have thixotropy. Therefore, even when the shaving agent is initially in a foam form (for example, when spraying a shaving agent composition) rather than being initially in a gel form and then foamed, a fine foam can be formed.

[0055] In particular, introducing a carbamate together with a phosphorous acid ester further improves transparency and viscosity. In this regard, improving the transparency of the phosphorous acid-modified fine fibers allows the initial gel to be provided in a desired color in shaving compositions and the like that are initially ejected as a gel. Furthermore, carbamates have amino groups. Therefore, the introduction of carbamates also results in a positive charge. Therefore, the introduction of carbamates is thought to enhance the charge interaction between the phosphorous acid ester and the carbamate, thereby improving viscosity. When the viscosity of the phosphorous acid-modified fine fibers is improved, the viscosity of a shaving agent composition containing the phosphorous acid-modified fine fibers is also improved. As a result, the stability of the gel at the time of ejection (e.g., preventing the gel from running down, etc.) can be improved, the foaming amount of the shaving agent that subsequently foams can be increased, and foaming stability (maintenance of the foamed state) can be improved. Furthermore, because the phosphorous acid-modified fine fibers are thixotropic, the gel at the time of ejection is stable, yet has excellent spreadability and is also good for razor glide. Furthermore, when the shaving composition is sprayed using compressed gas, the foam formed by spraying can be made finer.

[0056] The amount of phosphorous acid ester introduced is more than 2.0 mmol per 1 g of cellulose fiber, preferably 2.1 mmol or more, and more preferably 2.2 mmol or more. If the amount introduced is 2.0 mmol or less, the cellulose fiber may not be easily defibrated (when modified prior to defibration). In addition, the aqueous dispersion of cellulose fiber may become unstable. On the other hand, the amount of phosphorous acid ester introduced is preferably 3.39 mmol or less per 1 g of cellulose fiber. If the amount introduced exceeds 3.39 mmol, the cellulose fiber may dissolve in water.

[0057] The amount of phosphorous acid ester incorporated is a value evaluated based on elemental analysis, which is performed using an X-Max 50 001 manufactured by Horiba, Ltd.

[0058] The amount of phosphorous acid ester incorporated is a value evaluated based on elemental analysis, which is performed using an X-Max 50 001 manufactured by Horiba, Ltd.

[0059] The amount of carbamate introduced is preferably 0.06 to 2.34 mmol, more preferably 0.15 to 1.28 mmol, and particularly preferably 0.39 to 1.02 mmol per gram of cellulose fine fibers. If the amount introduced is less than 0.06 mmol, the light transmittance and viscosity of the dispersion may not be sufficiently increased. On the other hand, if the amount introduced exceeds 2.34 mmol, the cellulose fibers may dissolve in water. The amount of carbamate introduced is calculated by the Kjeldahl method.

[0060] The above describes the cases where the fine fibers are unmodified, and the cases where they are modified with phosphorous acid or carbamate. However, it is also preferable to modify (esterify) the cellulose fibers with a general phosphorus oxo acid. Esterification with a phosphorus oxo acid can be performed, for example, by the method described in JP 2019-199671 A.

[0061] In the fine fibers esterified with phosphorus oxoacid, a portion of the hydroxy groups of the cellulose fibers is preferably substituted with the functional group shown in the following structural formula (2): The amount of the functional group shown in structural formula (2) introduced is more than 2.0 mmol / g, preferably 2.1 mmol / g or more, more preferably 2.2 mmol / g or more, per gram of cellulose fibers.

[0062] [ka]

[0063] In structural formula (2), a, b, m, and n are natural numbers.

[0064] At least one of A1, A2,..., An, and A' is O, and the rest are R, OR, NHR, or none. R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, or a group derived from any of these. α is a cation composed of an organic or inorganic substance.

[0065] The esterification reaction with phosphorus oxoacids proceeds by adding additives such as phosphorus oxoacids or metal salts of phosphorus oxoacids to cellulose fibers and heating the mixture. Examples of additives include phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, ammonium polyphosphate, lithium dihydrogen phosphate, trilithium phosphate, dilithium hydrogen phosphate, lithium pyrophosphate, lithium polyphosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium polyphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium polyphosphate, phosphorous acid, sodium hydrogen phosphite, ammonium hydrogen phosphite, potassium hydrogen phosphite, sodium dihydrogen phosphite, sodium phosphite, lithium phosphite, potassium phosphite, magnesium phosphite, calcium phosphite, triethyl phosphite, triphenyl phosphite, and other phosphorous compounds such as pyrophosphorous acid. These additives can be used alone or in combination.

[0066] The fiber width of the fine fibers (average diameter of a single fiber) is preferably 1 to 1,000 nm, more preferably 1 to 500 nm, and particularly preferably 2 to 100 nm, whether the fine fibers are phosphorus oxoacid-modified fine fibers, phosphorous acid-modified fine fibers, or unmodified fine fibers (the same applies hereinafter). If the fiber width is less than 1 nm, the fibers may dissolve in water and lose the physical properties required for cellulose fine fibers, such as viscosity, thixotropy, strength, rigidity, and dimensional stability. On the other hand, if the fiber width exceeds 1,000 nm, the uniformity of the fibers may be impaired, which may be the main cause of a foreign body sensation when the fibers come into contact with the skin and may increase the number of missed shaves. Furthermore, thixotropy and other properties may not be exhibited.

[0067] The fiber width of the fine fibers is measured using an electron microscope as follows. First, 100 ml of an aqueous dispersion of fine fibers with a solid content of 0.01 to 0.1% by mass is filtered through a Teflon (registered trademark) membrane filter and solvent-substituted once with 100 ml of ethanol and three times with 20 ml of t-butanol. The sample is then freeze-dried and osmium-coated to obtain a sample. This sample is then observed using an SEM image at a magnification of 5,000x, 10,000x, or 30,000x, depending on the width of the fibers constituting it. In this observation, two diagonal lines are drawn on the observed image, and three additional straight lines are arbitrarily drawn passing through the intersections of the diagonal lines. The widths of a total of 100 fibers intersecting with these three straight lines are then visually measured. The median diameter of this measurement is taken as the fiber width.

[0068] The average fiber length of the fine fibers (single fiber length) is preferably 1 to 5,000 μm, more preferably 2 to 4,000 μm, and particularly preferably 3 to 3,000 μm. If the average fiber length is less than 1 μm, the fibers may become less entangled, resulting in a lack of cushioning properties for the foam. On the other hand, if the average fiber length exceeds 5,000 μm, the fibers may aggregate.

[0069] The average fiber length of the fine fibers can be adjusted as desired by, for example, selecting pulp fibers, pre-treating, and micronizing treatment.

[0070] The average fiber length of the fine fibers is determined by visually measuring the length of each fiber in the same manner as in the case of the average fiber diameter, and the median length of the measured values ​​is taken as the average fiber length.

[0071] The axial ratio of the fine fibers (fiber length / fiber width) is preferably 3 to 1,000,000, more preferably 6 to 340,000, and particularly preferably 10 to 340,000. If the axial ratio is less than 3, the fibers are no longer considered fibrous, and the cushioning effect on the skin provided by the fibers may be lost, potentially increasing skin stress caused by the razor. On the other hand, if the axial ratio exceeds 1,000,000, the viscosity of the composition (slurry) may become too high and the composition may feel like a foreign body when applied.

[0072] The fibrillation rate of the fine fibers is preferably 1.0 to 30.0%, more preferably 1.5 to 20.0%, and particularly preferably 2.0 to 15.0%. If the fibrillation rate exceeds 30.0%, the contact area with water becomes too large, which may make dehydration difficult. On the other hand, if the fibrillation rate is less than 1.0%, there may be insufficient hydrogen bonding between fibrils, making it impossible to form a sufficient foam.

[0073] The fibrillation rate refers to the value obtained by disintegrating fine fibers in accordance with JIS-P-8220:2012 "Pulp Disintegration Method" and measuring the resulting disintegrated pulp using FiberLab. (Kajaani).

[0074] The pseudo particle size distribution curve of the fine fibers preferably has one peak. When there is one peak, the fine fibers have high uniformity in fiber length and fiber diameter, and excellent drying properties. Furthermore, high uniformity in fiber diameter and fiber length also leads to excellent dispersibility.

[0075] The peak value of the fine fibers is preferably 5 μm or more, more preferably 7 μm or more, and particularly preferably 9 μm or more. If the peak value is less than 5 μm, the fine fiber treatment must be carried out for a long time, which increases the production cost.

[0076] The peak value of the fine fibers is preferably 60 μm or less, more preferably 50 μm or less, and particularly preferably 30 μm or less. If the peak value exceeds 60 μm, the uniformity of the fiber diameter and fiber length tends to be poor.

[0077] The half width of the peak of the fine fibers is preferably 30 μm or less, more preferably 20 μm or less, and particularly preferably 15 μm or less. If the half width of the peak exceeds 30 μm, the uniformity of the fibers will be lacking.

[0078] The peak value of the fine fibers is measured in accordance with ISO-13320 (2009). More specifically, a particle size distribution analyzer (LA-960 laser diffraction / scattering particle size distribution analyzer manufactured by Horiba, Ltd.) is used to examine the volumetric particle size distribution of the aqueous dispersion of the fine fibers. The most frequent diameter of the fine fibers is then measured from this distribution. This most frequent diameter is taken as the peak value.

[0079] The crystallinity of the fine fibers is preferably 50 to 100%, more preferably 60 to 90%, and particularly preferably 65 to 85%. If the crystallinity is less than 50%, bubbles may not be sufficiently formed (foam formation).

[0080] The crystallinity can be adjusted, for example, by selecting pulp fibers, pre-treating, defibrating, etc.

[0081] The crystallinity is a value measured by X-ray diffraction in accordance with JIS-K0131 (1996) "General rules for X-ray diffraction analysis." Note that fine fibers have amorphous and crystalline portions, and the crystallinity refers to the proportion of crystalline portions in the entire fine fibers.

[0082] The light transmittance of the fine fibers (solution with a solid content of 0.2%) is preferably 40.0% or more, more preferably 70.0% or more, and particularly preferably 90.0% or more. If the light transmittance is less than 40.0%, the transparency may be deemed insufficient.

[0083] The light transmittance of the fine fibers can be adjusted by, for example, selecting the pulp fibers, pre-treating them, defibrating them, and the like.

[0084] The light transmittance of the fine fibers is a value obtained by measuring the transparency (transmittance of light from 350 to 880 nm) of a 0.2% (w / v) dispersion of the fine fibers using a Spectrophotometer U-2910 (Hitachi, Ltd.).

[0085] When the concentration of fine fibers is 1% by mass (w / w), the dispersion preferably has a Brookfield viscosity of 1,000 to 200,000 cps, and particularly preferably 10,000 to 100,000 cps. If the Brookfield viscosity is less than 1,000 cps, the foam may not be stable over time (foam maintenance). On the other hand, if the Brookfield viscosity exceeds 200,000 cps, the viscosity may be too high, resulting in insufficient fluidity of the ejected gel or other product (reduced applicability).

[0086] The B-type viscosity (solids concentration 1%) of dispersions containing fine fibers is a value measured in accordance with JIS-Z8803 (2011) "Method for measuring viscosity of liquids." B-type viscosity is the resistance torque when stirring the dispersion, and the higher the viscosity, the more energy is required for stirring.

[0087] The pulp viscosity of the fine fibers is preferably 2 cps or more, more preferably 4 cps or more. If the pulp viscosity of the fine fibers is less than 2 cps, it may be difficult to suppress aggregation of the fine fibers.

[0088] The pulp viscosity of the fine fibers is a value measured in accordance with TAPPI T 230.

[0089] The freeness of the fine fibers is preferably 500 ml or less, more preferably 300 ml or less, and particularly preferably 100 ml or less. If the freeness exceeds 500 ml, the viscosity improving effect may not be sufficiently obtained.

[0090] The freeness of the fine fibers is a value measured in accordance with JIS P8121-2 (2012).

[0091] The water retention of the fine fibers is preferably 250 to 500%, more preferably 300 to 450%, and particularly preferably 300 to 400%. If the water retention is less than 250%, fluidity and smoothness may be impaired. On the other hand, if the water retention exceeds 500%, drainage may be impaired. In this regard, the water retention of the fine fibers can be further reduced by substituting the hydroxy groups of the fibers with carbamate groups, thereby improving dewatering and drying properties.

[0092] The water retention of the fine fibers can be adjusted as desired by, for example, selecting the raw pulp, pre-treating it, defibrating it, and the like.

[0093] The water retention of the fine fibers is a value measured in accordance with JAPAN TAPPI No. 26 (2000).

[0094] The blending ratio of the fine fibers is preferably 0.1 to 5%, more preferably 0.3 to 5%, and particularly preferably 0.5 to 5%, calculated as solid content relative to the total composition. If the blending ratio is less than 0.1%, the effect of including the fine fibers may not be exerted. On the other hand, if the blending ratio is more than 5%, the viscosity may become too high, which may impair foaming properties.

[0095] (Method of manufacturing fine fibers) When producing phosphorous-modified fine fibers, an additive (A) consisting of at least one of phosphorous acids and metal phosphite salts, preferably an additive (B) consisting of at least one of urea and a urea derivative, is added to cellulose fibers, and the fibers are heated to introduce a phosphorous acid ester, preferably a phosphorous acid ester and a carbamate, into the cellulose fibers. The cellulose fibers into which the phosphorous acid ester or the like has been introduced are washed and then defibrated to obtain phosphorous-modified fine fibers. However, the introduction of the phosphorous acid ester or carbamate may be performed after defibration (micronization). On the other hand, when producing unmodified fine fibers, only defibration is performed without using additives (A) and (B). When introducing a phosphorus oxoacid ester, an additive such as a phosphorus oxoacid or a metal salt of phosphorus oxoacid is added to cellulose fibers, and the fibers are heated and defibrated, as described above. The methods for defibrating unmodified fine fibers and phosphorus oxo acid-modified fine fibers are the same as those for producing phosphorous acid-modified fine fibers, so the following description will be given taking the case of producing phosphorous acid-modified fine fibers as an example.

[0096] (cellulose fiber) As the raw material cellulose fiber, for example, plant-derived fiber (plant fiber), animal-derived fiber, microbial-derived fiber, etc. can be used. These fibers can be used alone or in combination as needed. However, as the cellulose fiber, plant fiber is preferably used, and pulp fiber, which is a type of plant fiber, is more preferably used. When the cellulose fiber is pulp fiber, it is easy to adjust the physical properties of the phosphorous acid-modified fine fiber (fine fiber).

[0097] Examples of plant fibers that can be used include wood pulp made from broad-leaved trees, conifers, etc., non-wood pulp made from straw, bagasse, etc., and recycled paper pulp (DIP) made from recycled waste paper, broke, etc. These fibers can be used alone or in combination.

[0098] Examples of wood pulp that can be used include chemical pulps such as hardwood kraft pulp (LKP) and softwood kraft pulp (NKP), thermal mechanical pulp (TMP), and recycled paper pulp (DIP). These pulps can be used alone or in combination.

[0099] Hardwood kraft pulp (LKP) may be bleached hardwood kraft pulp, unbleached hardwood kraft pulp, or semi-bleached hardwood kraft pulp. Softwood kraft pulp (NKP) may be bleached softwood kraft pulp, unbleached softwood kraft pulp, or semi-bleached softwood kraft pulp. Developed paper pulp (DIP) may be magazine waste paper pulp (MDIP), newspaper waste paper pulp (NDIP), corrugated paper pulp (WP), or other developed paper pulp.

[0100] (Additive (A)) The additive (A) is composed of at least one of a phosphorous acid compound and a metal phosphite. Examples of the additive (A) that can be used include phosphorous acid compounds such as phosphorous acid, sodium hydrogen phosphite, ammonium hydrogen phosphite, potassium hydrogen phosphite, sodium dihydrogen phosphite, sodium phosphite, lithium phosphite, potassium phosphite, magnesium phosphite, calcium phosphite, triethyl phosphite, triphenyl phosphite, and pyrophosphorous acid. These phosphorous acid compounds or metal phosphite salts can be used alone or in combination. However, sodium hydrogen phosphite is preferred.

[0101] When adding the additive (A), the cellulose fibers may be in a dry state, a wet state, or a slurry state. The additive (A) may be in a powder state or an aqueous solution state. However, it is preferable to add the additive (A) in an aqueous solution state to the dry cellulose fibers because this ensures a high degree of reaction uniformity.

[0102] The amount of additive (A) added is preferably 1 to 10,000 g, more preferably 100 to 5,000 g, and particularly preferably 300 to 1,500 g per kg of cellulose fiber. If the amount added is less than 1 g, the effect of adding additive (A) may not be obtained. On the other hand, if the amount added exceeds 10,000 g, the effect of adding additive (A) may plateau.

[0103] (Additive (B)) The additive (B) is composed of at least one of urea and a urea derivative. Examples of the additive (B) that can be used include urea, thiourea, biuret, phenylurea, benzylurea, dimethylurea, diethylurea, and tetramethylurea. These ureas or urea derivatives can be used alone or in combination. However, it is preferable to use urea.

[0104] When the additive (B) is heated, it decomposes into isocyanic acid and ammonia as shown in the following reaction formula (1). The isocyanic acid is highly reactive and forms carbamate groups on the hydroxyl groups of cellulose as shown in the following reaction formula (2).

[0105] NH2-CO-NH2→ HN=C=O+NH3…(1)

[0106] Cell-OH+HN=C=O → Cell-CO-NH2…(2)

[0107] The amount of additive (B) added is preferably 0.01 to 100 mol, more preferably 0.2 to 20 mol, and particularly preferably 0.5 to 10 mol per mol of additive (A). If the amount added is less than 0.01 mol, the carbamate may not be sufficiently introduced into the cellulose fiber. On the other hand, if the amount added exceeds 100 mol, the effect of adding urea may plateau.

[0108] (heating) The heating temperature when heating the cellulose fiber to which the additives (A) and (B) have been added is preferably 100 to 210°C, more preferably 100 to 200°C, and particularly preferably 100 to 180°C. If the heating temperature is 100°C or higher, a phosphorous ester can be introduced. However, if the heating temperature exceeds 210°C, the cellulose may deteriorate rapidly, which may cause discoloration or a decrease in viscosity.

[0109] The pH when heating the cellulose fiber to which the additives (A) and (B) have been added is preferably 3 to 12, more preferably 4 to 11, and particularly preferably 6 to 9. The lower the pH, the easier it is to incorporate the phosphorous ester and carbamate. However, if the pH is less than 3, there is a risk that cellulose degradation will proceed rapidly.

[0110] The cellulose fibers containing the additives (A) and (B) are preferably heated until they are dry. Specifically, the cellulose fibers are dried until their moisture content is preferably 10% or less, more preferably 0.1% or less, and particularly preferably 0.001% or less. Of course, the cellulose fibers may be in an absolutely dry state, free of moisture.

[0111] The heating time for the cellulose fibers containing the additives (A) and (B) is, for example, 1 to 1,440 minutes, preferably 10 to 180 minutes, and more preferably 30 to 120 minutes. If the heating time is too long, the introduction of phosphorous acid esters or carbamates may proceed too quickly. Furthermore, if the heating time is too long, the cellulose fibers may turn yellow.

[0112] As a device for heating the cellulose fibers to which the additives (A) and (B) have been added, for example, a hot air dryer, a paper machine, a dry pulp machine, etc. can be used.

[0113] (Pretreatment) Before and / or after the introduction of the phosphorous acid ester or the like into the cellulose fibers, the cellulose fibers can be subjected to a defibration pretreatment such as beating, if necessary. By subjecting the pulp fibers to a pretreatment before defibration of the cellulose fibers, the number of defibrations can be significantly reduced, and the energy required for defibration can be saved.

[0114] The pretreatment of the cellulose fibers can be carried out by a physical method or a chemical method, preferably by a physical method and a chemical method. The pretreatment by a physical method and the pretreatment by a chemical method can be carried out simultaneously or separately.

[0115] Beating is preferably used as a physical pretreatment. Beating cellulose fibers cuts them into uniform pieces. This prevents entanglement of the cellulose fibers (prevents aggregation). From this perspective, beating is preferably carried out until the freeness of the cellulose fibers is 700 ml or less, more preferably 500 ml or less, and particularly preferably 300 ml or less.

[0116] The freeness of the cellulose fibers is a value measured in accordance with JIS P8121-2 (2012). Beating can be carried out using, for example, a refiner or a beater.

[0117] Examples of chemical pretreatments include hydrolysis of polysaccharides with acid (acid treatment), hydrolysis of polysaccharides with enzymes (enzyme treatment), swelling of polysaccharides with alkali (alkali treatment), oxidation of polysaccharides with an oxidizing agent (oxidation treatment), and reduction of polysaccharides with a reducing agent (reduction treatment). However, as a chemical pretreatment, enzyme treatment is preferred, and it is more preferred to additionally perform one or more treatments selected from acid treatment, alkali treatment, and oxidation treatment. Enzyme treatment and alkali treatment will be explained below in order.

[0118] The enzymes used in the enzymatic treatment are preferably at least one of cellulase enzymes and hemicellulase enzymes, and more preferably both. The use of these enzymes makes it easier to defibrate cellulose fibers. Cellulose enzymes decompose cellulose in the presence of water. Hemicellulase enzymes decompose hemicellulose in the presence of water.

[0119] Examples of cellulase enzymes that can be used include enzymes produced by species of the genera Trichoderma (filamentous fungi), Acremonium (filamentous fungi), Aspergillus (filamentous fungi), Phanerochaete (basidiomycetes), Trametes (basidiomycetes), Humicola (filamentous fungi), Bacillus (bacteria), Schizophyllum (basidiomycetes), Streptomyces (bacteria), and Pseudomonas (bacteria). These cellulase enzymes are available as reagents or commercially available products. Examples of commercially available products include Celluleucin T2 (manufactured by HPI), Meicerase (manufactured by Meiji Seika Kaisha), Novozym 188 (manufactured by Novozym), Multifect CX10L (manufactured by Genencor), and cellulase enzyme GC220 (manufactured by Genencor).

[0120] In addition, as the cellulase enzyme, either EG (endoglucanase) or CBH (cellobiohydrolase) can be used. EG and CBH can be used alone or in combination. They can also be used in combination with a hemicellulase enzyme.

[0121] Examples of hemicellulase enzymes that can be used include xylanase, which is an enzyme that breaks down xylan, mannase, which is an enzyme that breaks down mannan, and arabanase, which is an enzyme that breaks down araban. Also usable is pectinase, which is an enzyme that breaks down pectin.

[0122] Hemicellulose is a polysaccharide excluding pectins found between the cellulose microfibrils of plant cell walls. Hemicellulose is diverse and varies depending on the type of wood and the wall layers of the cell wall. Glucomannan is the main component in the secondary walls of softwoods, while 4-O-methylglucuronoxylan is the main component in the secondary walls of hardwoods. Therefore, when obtaining cellulose fine fibers from softwood bleached kraft pulp (NBKP), it is preferable to use mannase. Furthermore, when obtaining cellulose fine fibers from hardwood bleached kraft pulp (LBKP), it is preferable to use xylanase.

[0123] The amount of enzyme added to cellulose fibers is determined by, for example, the type of enzyme, the type of wood used as raw material (coniferous or broad-leaved), the type of mechanical pulp, etc. However, the amount of enzyme added to cellulose fibers is preferably 0.1 to 3 mass%, more preferably 0.3 to 2.5 mass%, and particularly preferably 0.5 to 2 mass%. If the amount of enzyme added is less than 0.1 mass%, the effect of adding the enzyme may not be fully obtained. On the other hand, if the amount of enzyme added exceeds 3 mass%, cellulose may be saccharified, resulting in a decrease in the yield of cellulose fine fibers. Another problem is that the improvement in effect may not be commensurate with the increase in the amount added.

[0124] When a cellulase enzyme is used as the enzyme, the pH during the enzymatic treatment is preferably in the weak acidic range (pH = 3.0 to 6.9) from the viewpoint of the reactivity of the enzymatic reaction, whereas when a hemicellulase enzyme is used as the enzyme, the pH during the enzymatic treatment is preferably in the weak alkaline range (pH = 7.1 to 10.0).

[0125] The temperature during the enzyme treatment is preferably 30 to 70°C, more preferably 35 to 65°C, and particularly preferably 40 to 60°C, regardless of whether a cellulase enzyme or a hemicellulase enzyme is used as the enzyme. If the temperature during the enzyme treatment is 30°C or higher, the enzyme activity is less likely to decrease, and prolonged treatment time can be prevented. On the other hand, if the temperature during the enzyme treatment is 70°C or lower, deactivation of the enzyme can be prevented.

[0126] The time for the enzyme treatment is determined depending on, for example, the type of enzyme, the temperature of the enzyme treatment, the pH during the enzyme treatment, etc. However, the time for the enzyme treatment is generally 0.5 to 24 hours.

[0127] After the enzymatic treatment, it is preferable to inactivate the enzyme. Examples of methods for inactivating the enzyme include adding an alkaline aqueous solution (preferably pH 10 or higher, more preferably pH 11 or higher) and adding hot water at 80 to 100°C.

[0128] Next, the alkali treatment method will be described.

[0129] As a method of alkali treatment, for example, there is a method in which cellulose fibers to which an ester of phosphorous acid or the like has been introduced are immersed in an alkaline solution.

[0130] The alkaline compound contained in the alkaline solution may be an inorganic alkaline compound or an organic alkaline compound. Examples of inorganic alkaline compounds include hydroxides of alkali metals or alkaline earth metals, carbonates of alkali metals or alkaline earth metals, and phosphates of alkali metals or alkaline earth metals. Examples of alkali metal hydroxides include lithium hydroxide, sodium hydroxide, and potassium hydroxide. Examples of alkaline earth metal hydroxides include calcium hydroxide. Examples of alkali metal carbonates include lithium carbonate, lithium bicarbonate, potassium carbonate, potassium bicarbonate, sodium carbonate, and sodium bicarbonate. Examples of alkaline earth metal carbonates include calcium carbonate. Examples of alkali metal phosphates include lithium phosphate, potassium phosphate, trisodium phosphate, and disodium hydrogen phosphate. Examples of alkaline earth metal phosphates include calcium phosphate and calcium hydrogen phosphate.

[0131] Examples of organic alkali compounds include ammonia, aliphatic amines, aromatic amines, aliphatic ammonium, aromatic ammonium, heterocyclic compounds, and their hydroxides, carbonates, phosphates, etc. Specific examples include ammonia, hydrazine, methylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, butylamine, diaminoethane, diaminopropane, diaminobutane, diaminopentane, diaminohexane, cyclohexylamine, aniline, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, pyridine, N,N-dimethyl-4-aminopyridine, ammonium carbonate, ammonium hydrogencarbonate, and diammonium hydrogenphosphate.

[0132] The solvent for the alkaline solution may be either water or an organic solvent, but is preferably a polar solvent (water, a polar organic solvent such as alcohol), and more preferably an aqueous solvent containing at least water.

[0133] The pH of the alkaline solution at 25°C is preferably 9 or higher, more preferably 10 or higher, and particularly preferably 11 to 14. When the pH is 9 or higher, the yield of cellulose fine fibers increases. However, when the pH exceeds 14, the handling of the alkaline solution decreases.

[0134] (Washing) It is preferable to wash the cellulose fibers into which a phosphorous acid ester or the like has been introduced prior to defibration. By washing the cellulose fibers, by-products and unreacted substances can be washed away. Furthermore, if this washing is performed prior to the alkaline treatment in the pretreatment, the amount of alkaline solution used in the alkaline treatment can be reduced.

[0135] The cellulose fibers can be washed using, for example, water or an organic solvent.

[0136] (defibration) The cellulose fibers to which phosphorous acid esters or the like have been introduced are defibrated (refining treatment) after washing. This defibration process microfibrillates the pulp fibers, turning them into cellulose fine fibers (cellulose nanofibers and microfiber cellulose). This defibration method is the same for unmodified fine fibers and phosphorus oxo acid-modified fine fibers.

[0137] When defibrating cellulose fibers, it is preferable to prepare the cellulose fibers in a slurry state. The solid content of this slurry is preferably 0.1 to 20% by mass, more preferably 0.5 to 10% by mass, and particularly preferably 1.0 to 5.0% by mass. When the solid content is within the above range, the cellulose fibers can be defibrated efficiently.

[0138] Defibration of cellulose fibers can be carried out using one or more of the following means: homogenizers such as high-pressure homogenizers and high-pressure homogenizers; high-speed rotary homogenizers; grinders, millstone-type friction machines such as attritors; refiners such as conical refiners and disc refiners; single-shaft kneaders; multi-shaft kneaders; and various bacteria. However, defibration of cellulose fibers is preferably carried out using a device or method that uses a water flow, particularly a high-pressure water flow, to refine the fibers. This device or method results in extremely uniform dimensional and uniform dispersion of the resulting cellulose fine fibers. In contrast, using a grinder that grinds the fibers between rotating grindstones, for example, makes it difficult to uniformly refine the cellulose fibers, and in some cases, there is a risk that some undisintegrated fiber clumps may remain.

[0139] Grinders used to defibrate cellulose fibers include, for example, the Masscolloider manufactured by Masuko Sangyo Co., Ltd. Devices that use high-pressure water flow to pulverize the fibers include, for example, Starburst (registered trademark) manufactured by Sugino Machine Co., Ltd. and Nanovater (registered trademark) manufactured by Yoshida Kikai Kogyo Co., Ltd. High-speed rotary homogenizers used to defibrate cellulose fibers include the Clearmix-11S manufactured by M Technique Co., Ltd.

[0140] It has been found that when cellulose fibers are defibrated using both the method of grinding between rotating grinding wheels and the method of refining with a high-pressure water jet, and the resulting fibers are observed under a microscope, the fibers obtained using the method of refining with a high-pressure water jet have a more uniform fiber width.

[0141] Defibration using a high-pressure water stream is preferably carried out by pressurizing a cellulose fiber dispersion using a pressure intensifier to, for example, 30 MPa or more, preferably 100 MPa or more, more preferably 150 MPa or more, and particularly preferably 220 MPa or more (high-pressure conditions), spraying it from a nozzle with a pore diameter of 50 μm or more, and then reducing the pressure to, for example, 30 MPa or more, preferably 80 MPa or more, and more preferably 90 MPa or more (reduced-pressure conditions). The pulp fibers are defibrated by the cleavage phenomenon caused by this pressure difference. If the pressure under the high-pressure conditions is low or if the pressure difference from the high-pressure conditions to the reduced-pressure conditions is small, the defibration efficiency decreases, and repeated defibration (spraying from the nozzle) becomes necessary to achieve the desired fiber diameter.

[0142] As a device for defibrating using a high-pressure water stream, it is preferable to use a high-pressure homogenizer. A high-pressure homogenizer is a homogenizer capable of ejecting a cellulose fiber slurry at a pressure of, for example, 10 MPa or more, preferably 100 MPa or more. When cellulose fibers are treated with a high-pressure homogenizer, collisions between the cellulose fibers, pressure differences, microcavitation, and the like act to effectively defibrate the cellulose fibers. Therefore, the number of defibration treatments can be reduced, and the production efficiency of cellulose fine fibers can be improved.

[0143] The high-pressure homogenizer used is preferably one that causes cellulose fiber slurry to collide in a straight line against each other. Specifically, for example, a counter-collision type high-pressure homogenizer (MICROFLUIDIZER (registered trademark), wet jet mill) is used. In this device, two upstream flow paths are formed so that the pressurized cellulose fiber slurry collides against each other at the confluence. The cellulose fiber slurry collides at the confluence, and the collided cellulose fiber slurry flows out from the downstream flow path. The downstream flow path is arranged perpendicular to the upstream flow path, and the upstream and downstream flow paths form a T-shaped flow path. When such a counter-collision type high-pressure homogenizer is used, the energy applied from the high-pressure homogenizer is converted to collision energy to the maximum extent possible, allowing for more efficient defibration of cellulose fibers.

[0144] The cellulose fibers are preferably defibrated so that the average fiber width, average fiber length, water retention, crystallinity, peak value of pseudo-particle size distribution, pulp viscosity, etc. of the resulting cellulose fine fibers (such as phosphorous acid-modified fine fibers) attain the desired values ​​or evaluations described above. [Example]

[0145] Next, an embodiment of the present invention will be described. To clarify the presence or absence of fine fibers and the influence of surfactants, shaving foams were prepared at the blending ratios shown in Table 1 and subjected to a lathering test. Details of the phosphorous-modified fine fibers, unmodified fine fibers, and other ingredients, as well as details of the evaluation items, are as follows. Note that the blending ratios shown in the table are not the ratio of active ingredients but the ratio to all ingredients including water, etc.

[0146] (Phosphorous acid modified CNF (cellulose nanofiber)) 100g of a mixture of 13g of sodium hydrogen phosphite pentahydrate, 10.8g of urea, and 76.2g of water was mixed with 10g (dry weight) of raw pulp (NBKP: moisture content 98.0% by mass) and dried at 105°C. The dried pulp was reacted at 130°C for 2 hours. Next, water washing and filtration were repeated twice to obtain cellulose fibers (phosphite-modified pulp) incorporating esters of phosphorous acid containing inorganic cations. This phosphite-modified pulp was then pulverized (defibrated) using a high-pressure homogenizer to obtain phosphite-modified CNF (average fiber diameter: 3nm). The phosphite-modified CNF was blended with other ingredients as a 1.0% by mass slurry.

[0147] (Unmodified CNF) The bleached hardwood pulp was roughly defibrated using a single-disc refiner, and then refined (defibrated) using a high-pressure homogenizer to obtain a fiber (average fiber diameter: 50 nm). Unmodified CNF was also blended with other ingredients as a 0.2% by mass slurry.

[0148] (CMC) Daicel FineChem Co., Ltd. product number 1330 was used.

[0149] (sodium laurate) Sodium laurate manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. was used and adjusted to a 5% solution.

[0150] (sodium stearate) Sodium stearate manufactured by Fujifilm Wako Pure Chemical Industries was used.

[0151] (Sodium palmitate) Sodium palmitate manufactured by Fujifilm Wako Pure Chemical Industries was used.

[0152] The above sodium laurate (Na), sodium stearate (Na), and sodium palmitate (Na) were mixed at a solid content mass ratio of 90:5:5, and used after adjusting the concentration to 5%.

[0153] (α-olefin sulfonate) Lion Specialty Chemicals' Lipolan LB-440 was used and adjusted to a concentration of 5% active ingredient.

[0154] (glycerin) Refined glycerin from Sakamoto Pharmaceutical Co., Ltd. was used.

[0155] (phenoxyethanol) Phenoxyethanol-S from Yokkaichi Chemical Co., Ltd. was used.

[0156] (water) Purified water was used. In the table, water indicates the amount (g) of purified water.

[0157] (Foam height) Approximately 50 mL of the test liquid (shaving foam) was placed in a foaming spray bottle and then poured five times into a 100 mL beaker, and the height of the foam (mm) immediately after pouring into the beaker was measured.

[0158] (Foam viscosity evaluation) Approximately 50 mL of the test liquid (shaving foam) was placed in a foaming spray bottle, and a ruler was fixed to a transparent glass plate tilted at an angle of approximately 35 degrees as shown in Figure 1. The foam was dispensed at a point 20 cm away, and the foam's ability to slide down was visually observed. After 60 seconds, if the foam had slid down 10 cm or less, it was marked as ◯; if it had slid down more than 10 cm but not reached the 5 cm line, it was marked as △; if it had reached the 5 cm line, it was marked as ×. In Figure 1, foam (◯) indicates if the foam had slid down 10 cm or less, foam (△) indicates if it had slid down more than 10 cm but not reached the 5 cm line, and foam (×) indicates if it had reached the 5 cm line.

[0159] The results are shown in Table 1.

[0160] [Table 1]

[0161] (Consideration) Unmodified CNF tended to have high initial foaming (foaming) properties when combined with any surfactant. On the other hand, phosphorous-modified CNF, especially when used with a fatty acid salt surfactant, tended to produce viscous foam and long-lasting foam retention. Combining unmodified CNF and phosphorous-modified CNF tended to achieve both foaming and retention, while CMC produced foaming properties but with low foam viscosity. This suggests that the shaving composition of this invention can adjust foam viscosity and foaming properties by using either unmodified CNF or phosphorous-modified CNF, or both. [Industrial Applicability]

[0162] The present invention can be used as a foaming shaving agent such as a shaving foam or a shaving gel foam.

Claims

1. The present invention comprises cellulose fine fibers having an average fiber width of 1 to 1,000 nm and an axial ratio of 10 to 340,000, and a foaming component, The cellulose fine fibers include fine fibers in which some or all of the hydroxy groups have been modified with an ester of phosphorus oxoacid, and unmodified fine fibers, Contains sulfonic acid type surfactants, A shaving composition comprising:

2. the phosphorus oxoacid is phosphorous acid; The amount of the phosphorous acid ester introduced is more than 2.0 mmol / g; The shaving composition of claim 1.

3. The foaming component contains at least one anionic surfactant selected from a carboxylic acid type surfactant, a sulfonic acid type surfactant, a sulfate ester type surfactant, a phosphate ester type surfactant, and an amino acid type surfactant. The shaving composition according to claim 1 or 2.

4. The crystallinity of the cellulose fine fibers is 50 to 100%. The shaving composition according to any one of claims 1 to 3.

5. The B-type viscosity of a dispersion having a concentration of the cellulose fine fibers of 1% by mass is 1,000 to 200,000 cps. The shaving composition according to any one of claims 1 to 4.

6. The average fiber length of the cellulose fine fibers is 3 to 5,000 μm. The shaving composition according to any one of claims 1 to 5.

7. The ratio of the phosphorous acid-modified fine fibers to the entire composition is 1 to 20 mass%. The shaving composition according to claim 2.

Citation Information

Patent Citations

  • Improvements in or relating to foamable compositions

    GB1015917A

  • JP1965-006118B

  • Gradually foaming type late foaming composition

    JP1990247115A

  • Post-foamable aerosol composition

    JP1995163861A

  • Cosmetic composition containing fine fibrous cellulose and / or its composite material

    JP2009062332A